A Three‐Component Assembly Promoted by Boronic Acids Delivers a Modular Fluorophore Platform (BASHY Dyes)1. Issue 5 (22nd December 2015) - Santos, Fábio M. F.; Rosa, João N.; Candeias, Nuno R.; Carvalho, Cátia Parente; Matos, Ana I.; Ventura, Ana E.; Florindo, Helena F.; Silva, Liana C.; Pischel, Uwe; Gois, Pedro M. P.
Abstract: The modular assembly of boronic acids with Schiff‐base ligands enabled the construction of innovative fluorescent dyes [boronic acid salicylidenehydrazone (BASHY)] with suitable structural and photophysical properties for live cell bioimaging applications. This reaction enabled the straightforward synthesis (yields up to 99 %) of structurally diverse and photostable dyes that exhibit a polarity‐sensitive green‐to‐yellow emission with high quantum yields of up to 0.6 in nonpolar environments. These dyes displayed a high brightness (up to 54 000 m −1  cm −1 ). The promising structural and fluorescence properties of BASHY dyes fostered the preparation of non‐cytotoxic, stable, and highly fluorescent poly(lactide‐ co ‐glycolide) nanoparticles that were effectively internalized by dendritic cells. The dyes were also shown to selectively stain lipid droplets in HeLa cells, without inducing any appreciable cytotoxicity or competing plasma membrane labeling; this confirmed their potential as fluorescent stains. Abstract : Anything but boring : Boronic acids are used as configurational blocks in the construction of a structurally diverse platform of polarity‐sensitive fluorescent dyes that are suitable for the bioimaging of nonpolar environments, such as lipid droplets.